EVALUASI AKTIVITAS TABIR SURYA EKSTRAK ETANOL DAUN GENJER (Limnocharis flava) SECARA SPEKTROFOTOMETRI - Haryanti, Pipin Dwi; Kurniawati, Zenia Lutfi; Rahmadani, Agung (Lantanida Journal, 2026)
The dangers of ultraviolet (UV) radiation exposure to skin health have triggered the need for safe natural sunscreen ingredients. This study aims to assess the efficacy of ethanol extract of genjer leaves (Limnocharis flava) as an active ingredient in sunscreen preparations, with an emphasis on the analysis of SPF values ​​and total flavonoid levels. The methodology used is an in vitro laboratory experiment. The extraction procedure was carried out through a maceration technique using 96% ethanol solvent (1:10 ratio). Flavonoid levels were measured using the AlCl3 colorimetric method with quercetin as the standard, while SPF calculations were carried out via a UV-Vis spectrophotometer in the range of 290–320 nm with varying levels of 200, 400, and 600 ppm. The research data revealed that the extract contained a total flavonoid content of 267.58 ± 1.21 mg QE/g with a yield of 18.2%. The study results confirmed a unidirectional correlation between the extract concentration level and skin protection power. The most optimal effectiveness was detected at a concentration of 600 ppm, which resulted in an SPF of 15.46 (ultra protection). Furthermore, the erythema transmission (%Te) value of 3.38% and pigmentation (%Tp) of 2.66% placed this extract in the sunscreen category. In conclusion, genjer leaves have very promising prospects as a natural sunscreen component due to their capability to absorb both UV-A and UV-B radiation simultaneously.